Open Access Scientific Evidence of Cognitive Behavioral Therapy for Patients with Fibromyalgia - Gómez-de-Regil, Lizzette (2016)
Objective: To provide a summary of scientific open access resources Cognitive Behavioral Therapy interventions in patients with fibromyalgia. Method: Bibliographical search performed in Pubmed and PsycInfo, Latindex, Scielo and Redalyc online databases. No year of publication criterion was applied. Results: 377 citations were reduced to a list of 59 relevant publications, from 1993 to 2016. Most studies were performed in adult samples, in Spain or the United States, with pre-post quantitative design. Only 15 publications were open access. Conclusions: Empirical evidence is ample, yet mostly restricted. Open access material might promote interest in and encourage the design, implementation and evaluation of CBT interventions in the benefit of fibromyalgia patients, the health system and science.